PELATIHAN PEMBUATAN DAN APLIKASI PUGATI UNTUK BIBIT GAHARU PADA KELOMPOK WANITA TANI DEDARE GAWAH DI PUSUK LESTARI LOMBOK BARAT - Ernin Hidayati; Sarkono Sarkono; Juarsahnim Juarsahnim; Moh. Andi Setiawan; Bambang Fajar Suryadi; Faturrahman Faturrahman (Universitas Mataram, 2023)
Currently, an ex-situ agarwood conservation effort was conducted in the Pusuk Lestari Forest, West Lombok by importing the plant varieties from outside the area. The difference of climate between the origin and destination areas makes the seedlings susceptible to stress and so they need to be acclimatized. Microbial organic-biological fertilizer (PUGATI) is applied to healthy and stimulating the growth of the seedlings during the acclimatization process. Microbial organic-biological fertilizer (PUGATI) is applied to healthy and stimulating the growth of the seedlings during the acclimatization process. This activity aims to increase the knowledge and skills of the Dedare Gawah Women Farmers Group in Pusuk Lestari Village to produce and application of PUGATI. The activity was carried out in November 2022 at Pusuk Lestari Village. The main activities are carried out in four steps: knowledge transfer by lectures, skills transfer by group practice and PUGATI applications, and also planting agarwood seedlings. The lecture was delivered by the dedication team. The team of community service presented a lecture. The practice of producing PUGATI is carried out in groups. The PUGATI application is carried out directly on the gaharu seedlings at the time of planting in the Pusuk Lestari Forest. Participants took part in all steps of the activities enthusiastically characterized by the many questions raised from the participants. Participants are able to carry out the practice of produced PUGATI correctly and precisely. All participants appreciated this activity because the knowledge and skill of PUGATI applicable not only to agarwood seedlings but also to other plants. This is in line with the participant daily activities, such as planting vegetables and fruit. Participants considered that this activity was very useful because it provided new knowledge and skills for them.